Дослідження параметрів водно-спиртових сумішей отриманих в умовах знакозмінних імпульсів тиску - Шурчкова, Юлія Олександрівна; Дубовкіна, Ірина Олександрівна (НТУ "ХПІ", 2015)
Проведено дослідження фізико-хімічних параметрів, а саме кількості шкідливих домішок: 1-пропанолу, 2-пропанолу, ацетальдегіду, метанолу, у водно-спиртових сумішах, які були одержані в умовах знакозмінних імпульсів тиску із застосуванням роторно-пульсаційного апарату, в якому реалізована основна концепція дискретно-імпульсного введення енергії. Визначені основні фактори, а саме: час оброблення, температура вихідних компонентів, напруження зсуву потоку, швидкості зсуву потоку, високочастотні осциляції та коливання, які впливають на кількість шкідливих домішок.

Researches parameters, namely, the amount of harmful impurities: 1-propanol, 2-propanol, acetaldehyde, methanol, water-ethanol mixtures obtained under alternating pressure pulses using hardware which implements the basic concept of the discrete-pulsed energy input. As a result of chromatographic researches of water-ethanol mixtures in wide concentration range was set reduction of harmful impurities without the introduction of additional chemicals impurities. Obtained the water-ethanol mixture with improved physic-chemical parameters. When using the technology of production for water-ethanol mixtures in conditions of alternating pressure pulse is intense impact stress sheal, shear flow, high-frequency oscillations, which leads to reduction of quantity of harmful impurities. It shows the dependence of harmful impurities on the temperature and the method of treatment of water-ethanol mixtures. It has been established the optimum temperature of the mixing process of water and ethanol in conditions of alternating pressure pulse. The main factors affecting the amount of harmful impurities.
The investigating of parameters water-ethanol mixtures obtained under alternating impulses of pressure
Keywords: процес гідратації; роторно-пульсаційний апарат; дискретно-імпульсне введення енергії; РПА; process of hydration; rotary-pulsation apparatus